Nonperturbative Strange Sea in Proton Using Wave Functions Inspired by Light Front Holography - Vega A. Alfredo; Gutsche Th. Thomas; Schmidt I. A. Ivan; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2016, 2016)
Title screen